Menstrual cycles and the impact upon performance in elite British track and field athletes: a longitudinal study - Jones, B.; L`Heveder, A.; Bishop, C.; Kasaven, L.; Saso, S.; Davies, S.; Chakraverty, R.; Brown, J.; Pollock, N. (Frontiers in Sports and Active Living, 2024)
Objective: To assess the prevalence of menstrual disorders and the perceived effect of menstrual cycles upon performance in elite athletes.